Associations between health-related fitness and patient-reported symptoms in newly diagnosed breast cancer patients - Ki-Yong An; Fernanda Z. Arthuso; Myriam Filion; Spencer J. Allen; Stephanie M. Ntoukas; Gordon J. Bell; Jessica McNeil; Qinggang Wang; Margaret L. McNeely; Jeff K. Vallance; Lin Yang; S. Nicole Culos-Reed; et al. (Elsevier, 2024)
Background: Newly diagnosed breast cancer patients experience symptoms that may affect their quality of life, treatment outcomes, and survival. Preventing and managing breast cancer-related symptoms soon after diagnosis is essential. The purpose of this study was to investigate the associations between health-related fitness (HRF) and patient-reported symptoms in newly diagnosed breast cancer patients. Methods: This study utilized baseline data from the Alberta Moving Beyond Breast Cancer Cohort Study that were collected within 90 days of diagnosis. HRF measures included peak cardiopulmonary fitness (peak volume of oxygen consumption (VO2peak)), maximal muscular strength and endurance, flexibility, and body composition. Symptom measures included depression, sleep quality, and fatigue. Adjusted multivariable logistic regression was performed for analyses. Results: Of 1458 participants, 51.5% reported poor sleep quality, 26.5% reported significant fatigue, and 10.4% reported moderate depression. In multivariable-adjusted models, lower relative VO2peak was independently associated with a greater likelihood of all symptom measures, including moderate depression (p < 0.001), poor sleep quality (p = 0.009), significant fatigue (p = 0.008), any symptom (p < 0.001), and multiple symptoms (p < 0.001). VO2peak demonstrated threshold associations with all symptom measures such that all 3 lower quartiles exhibited similar elevated risk compared to the highest quartile. The strength of the threshold associations varied by the symptom measure with odds ratios ranging from ∼1.5 for poor sleep quality to ∼3.0 for moderate depression and multiple symptoms. Moreover, lower relative upper body muscular endurance was also independently associated with fatigue in a dose-response manner (p = 0.001), and higher body weight was independently associated with poor sleep quality in an inverted U pattern (p = 0.021). Conclusion: Relative VO2peak appears to be a critical HRF component associated with multiple patient-reported symptoms in newly diagnosed breast cancer patients. Other HRF parameters may also be important for specific symptoms. Exercise interventions targeting different HRF components may help newly diagnosed breast cancer patients manage specific symptoms and improve outcomes.